2017
DOI: 10.1111/hel.12406
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter: Inflammation, immunology and vaccines

Abstract: Helicobacter pylori is usually acquired in early childhood and the infection persists lifelong without causing symptoms. In a small of cases, the infection leads to gastric or duodenal ulcer disease, or gastric cancer. Why disease occurs in these individuals remains unclear, however the host response is known to play a very important part. Understanding the mechanisms involved in maintaining control over the immune and inflammatory response is therefore extremely important. Vaccines against H. pylori have rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 49 publications
(89 reference statements)
0
8
0
1
Order By: Relevance
“…HP infection often occurs in early childhood and will last a patient's whole life, whereas only a small percentage of HP-infected patients have obvious symptoms. [ 37 ] A complex balance between the human immune system and the HP after HP infection develops, resulting in a long state of chronic infection. [ 3 38 ]…”
Section: Discussionmentioning
confidence: 99%
“…HP infection often occurs in early childhood and will last a patient's whole life, whereas only a small percentage of HP-infected patients have obvious symptoms. [ 37 ] A complex balance between the human immune system and the HP after HP infection develops, resulting in a long state of chronic infection. [ 3 38 ]…”
Section: Discussionmentioning
confidence: 99%
“…Even though both innate and acquired immune responses are activated in individuals infected with H. pylori, the host is unable to eradicate the bacteria, leading to a chronic lifelong infection (37,38). To escape the host's immune response and to survive in the hostile conditions found in the stomach, H. pylori has developed several strategies, including manipulating innate immune receptors and inhibiting effector T-cell responses (39,40).…”
Section: Helicobacter Pylori and Neurological Disordersmentioning
confidence: 99%
“…H. pylori infects >50% of the world population and may affect gastric physiology, via triggering gastritis and canceration processes (3). Treatment of H. pylori infection may therefore help prevent GC in the general population (4,5); however, this treatment appears to be unrelated to the prognosis of patients with early GC (5,6). Gastric biopsy of patients with gastrointestinal-related symptoms demonstrated that in addition to the common H. pylori-related gastritis, several other modes of mucosal damage are also increasing (7).…”
Section: Introductionmentioning
confidence: 99%